(untitled) (Journal of Universal Excellence, 2026)
Research question: This article provides an answer to the question: What kind of housing do the seniors in Slovenia prefer after a substantial decrease of their functional capacities, i.e. when they already need long-term care services? Purpose: During the study, the seniors participating in the study were still able to live in their current dwelling – in the home where they lived for years together with their family or alone; but because of a substantial decrease of their functional capacities they had become aware that it would be difficult to continue to stay there. We wanted to know where they would like to migrate or move to when needed, and what kind of housing should be provided on the housing market for these cohorts. Method: After our study of the relevant European and American literature we found that the construction of housing for seniors can be developed in different types of structures and that there is a substantial gap between the needs and the availabilities of housing arrangements in Slovenia, which also increases the rigidity of the Slovenian housing market and reduces land rent in comparison with USA and Western Europe. Seniors using long-term care services provided by municipalities in their own homes, living outside the main Slovenian central places, were included in the survey. To identify the preferred structure of the built environment for seniors we organised 3 groups of interviews with assisted living inhabitants from three Slovenian municipalities and evaluated the percentages of each desired type of housing and care. Results: The results show that more than half of Slovenian seniors do not have the possibility to move to retirement villages or other better adapted homes in assisted living housing units, where they could protect their dignity and independence better than in institutional care in nursing homes. Local administration and society: These findings refer to the local administration initiative to (a) built proper housing units for seniors with decreasing functional capacities themselves, or (b) to initiate investments in local areas that would, in turn, attract private investments in proper and affordable housing for seniors. Novelty: This study is the first of its kind in Slovenia while its results provide better insight into what matters most to Slovenian seniors regarding their housing arrangements. Further extension: The study could give different results in the case of metropolitan areas, e.g. for the case of Ljubljana.